Nutrition-sensitive value chains from a smallholder perspective: A framework for project design - Peña, Isabel de la; Garrett, James; Gelli, Aulo (International Fund for Agricultural Development, 2018)
The principal purpose of this literature review was, thus, to provide the conceptual basis for development of a framework and approach for the design of NSVC projects that seek to improve diet quality and nutrition for project beneficiaries, particularly smallholders. The framework and proposed steps for project design that resulted from the literature review were then used to structure fieldwork in Nigeria and Indonesia to test the approach and, ultimately, provide evidence and experience-based guidance for NSVC project design. The findings have been reflected in the resulting manual: Nutrition-sensitive value chains: A guide for project design (de la Peña and Garrett 2018).